The History of the Formation of the Concept of Guilt in Criminal Law - Airapetean, Artur; Tsonku, Sanda (Journal of Danubian Studies and Research, 2022)
The relevance of this study is predetermined by the trends in the growth of crime in modern society, the importance of legislative consolidation of the main provisions relating to the subjective side of the crime, forms of guilt, and their consideration in the individualization of punishment. Understanding the principle of guilt as a measure or degree of neglect of generally significant values or norms of behavior has a number of important social and legal consequences. The main of these consequences is that the measure of neglect can have a lot of shades, a large number of degrees, which must be taken into account not only when imposing punishment, but also in the process of qualifying a crime. It is impossible to reflect in the criminal law all the intellectual, strong-willed, emotional moments of such an attitude, the variety of their shades and combinations, the process of its formation. We can only talk about the most important of all this, i.e. about the essence of the combinations of these moments and the signs characterizing them, about the very result of the mental attitude of a person to a crime. It is in this connection that this study is aimed at studying the history of the formation of the concept of guilt in criminal law.